The Unity of Material Supposition: An Ockhamist Solution - Crimi, Milo (Recherches de théologie et philosophie médiévales, 2024)
William of Ockham’s Summa of Logic includes a sophisticated semantic theory based on the notion of supposition (suppositio). One part of this theory – material supposition (suppositio materialis) – concerns the mention or quotation, rather than use, of a linguistic expression. Ockham takes material supposition to transcend morphosyntactic and even lexical identity. For example, a written or spoken token of the nominative ‘hircus’ may supposit materially not only for other tokens of ‘hircus’, but also for tokens of the oblique ‘hirci’, ‘hirco’, ‘hircum’, and so on, the abstract ‘hircinitas’, the adjectival ‘hircinus’, the synonymous ‘caper’, the English ‘goat’, and so on. How is this possible? In other words, what unifies the range of material supposits (supposita) of a given term token? It has been suggested that this problem of unity is unsolvable using the resources of Ockham’s theory and that later developments in medieval semantics were made in order to repair the deficiency. To date, the most successful reply on Ockham’s behalf introduces relations of equiformity and grammatical similarity not explicitly present in his theory. I will argue that Ockham’s own semantic relations of signification (significatio) and subordination (subordinatio) are sufficient to achieve unity.